Prevalência de depressão e fatores associados em idosos institucionalizados em um município do interior de Minas Gerais - SANTIAGO, Victor dos Reis (2020)
to verify the factors associated with indicative of depression in institutionalized elderly people. Method: cross-sectional, quantitative study with 208 elderly people from long-term care facilities. Sociodemographic, economic and clinical data, self-perceived health, functional capacity, cognitive assessment and 8 indicative of depression were evaluated. The analysis has included absolute and relative frequency distributions, the t test, Pearson correlation and multiple linear regression (p<0.05) using SPSS. Results: Male gender has prevailed; White color; studied from one to five years; singles; use five medications or less; have up to four diseases; total or partial dependence on activities of daily living and a high percentage of cognitive decline and indicative of depression. The indicative of depression was associated with education and deambulation. Conclusion: Actions aimed at improving health, family and social life of the elderly people should be proposed in order to minimize the signs of depression.